2017
DOI: 10.1007/s00586-017-5032-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of the AOSpine Patient Reported Outcome Spine Trauma (AOSpine PROST): a universal disease-specific outcome instrument for individuals with traumatic spinal column injury

Abstract: Purpose To report on the multi-phase process used in developing the AOSpine Patient Reported Outcome Spine Trauma (AOSpine PROST), as well as the results of its application in a pilot study. Methods The International Classification of Functioning, Disability and Health (ICF) methodology was used as the basis for the development of this tool. Four preparatory studies and a consensus conference were performed, and resulted in the selection of 25 core ICF categories as well as the scale for use. The first draft o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We found this to be a grounded decision as pretesting was already performed for the Dutch version in a previous study. 19 As hypothesized, patients had no misunderstanding of the questions and no question was indicated as inapplicable. Patients provided very useful information on the general concept of AOSpine PROST: it was questioned whether they should also take the trauma-related injuries into account when scoring an item.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We found this to be a grounded decision as pretesting was already performed for the Dutch version in a previous study. 19 As hypothesized, patients had no misunderstanding of the questions and no question was indicated as inapplicable. Patients provided very useful information on the general concept of AOSpine PROST: it was questioned whether they should also take the trauma-related injuries into account when scoring an item.…”
Section: Discussionmentioning
confidence: 95%
“…17 18 Four preparatory studies, followed by an international consensus conference, led to the development of a Dutch version of AOSpine PROST. 19 In the developmental process of the AOSpine PROST we sought to focus on patients sustaining injuries to their spinal column and excluded completely paralyzed (ASIA impairment grade A or B at discharge from hospital) and polytrauma patients (Injury Severity Score [ISS] >15), to identify specific problems related to spine trauma. A validation study among traumatic spinal column injury patients in the Netherlands showed very good results.…”
mentioning
confidence: 99%
“…Subsequently, a draft Dutch version of the tool was developed by clustering the 25 core ICF categories into 19 items and implementing those into the selected 0-100 Numeric Rating Scale (NRS-101). After pilot testing, a definitive Dutch version to be validated was developed [8] In the developmental process and initial validation, we sought to focus on patients sustaining injuries to their spinal column and excluded completely paralyzed and polytrauma patients, to identify specific problems related to spine trauma. This study aimed to validate the Dutch version of the AOSpine PROST among traumatic spinal column injury patients.…”
Section: Introductionmentioning
confidence: 99%
“…We felt that this parameter would add a valuable contribution to the overall tool, and provide a direct connection to the patient's reported outcome as expressed by AOSpine PROST (Patient Reported Outcome Spine Trauma). This AOSpine PROST was developed and validated on the basis of different foundational studies and following an international consensus conference [25]. In general, fair to moderate results were observed for the inter-rater reliability of the tool, while the intra-rater reliability showed moderate to good results.…”
Section: Discussionmentioning
confidence: 99%